2017
DOI: 10.1038/labinvest.2017.59
|View full text |Cite
|
Sign up to set email alerts
|

Roflumilast reverses polymicrobial sepsis-induced liver damage by inhibiting inflammation in mice

Abstract: Sepsis is a life-threatening syndrome accompanied by an overwhelming inflammatory response and organ dysfunction. Selective targeting of phosphodiesterase 4 (PDE4) is currently being investigated as an effective therapeutic approach for inflammation-associated diseases. Roflumilast is a selective PDE4 inhibitor, used for the treatment of severe chronic obstructive pulmonary disease in clinic. However, its role in the treatment of sepsis-induced liver damage remains unclear. In the present study, we evaluated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 64 publications
0
20
0
1
Order By: Relevance
“…Based on these observations, our group later identified the alcohol-mediated increase of PDE4B as a cause of diminished cAMP levels and an underlying mechanism of alcohol-mediated “priming”; PDE4 inhibition abrogates alcohol-mediated “priming” of monocytes/macrophages and production of high levels of TNFα [92]. Protective effect of PDE4 inhibitors, Rolipram and roflumilast, has also been demonstrated in various murine models of inflammation-driven liver injury [161165]. Importantly, our recent study demonstrated that chronic alcohol feeding reduced hepatic cAMP leading to decreased phospho-CREB levels in a mouse ALD model [74].…”
Section: Therapeutic Interventions Via Camp Signalingmentioning
confidence: 99%
“…Based on these observations, our group later identified the alcohol-mediated increase of PDE4B as a cause of diminished cAMP levels and an underlying mechanism of alcohol-mediated “priming”; PDE4 inhibition abrogates alcohol-mediated “priming” of monocytes/macrophages and production of high levels of TNFα [92]. Protective effect of PDE4 inhibitors, Rolipram and roflumilast, has also been demonstrated in various murine models of inflammation-driven liver injury [161165]. Importantly, our recent study demonstrated that chronic alcohol feeding reduced hepatic cAMP leading to decreased phospho-CREB levels in a mouse ALD model [74].…”
Section: Therapeutic Interventions Via Camp Signalingmentioning
confidence: 99%
“…A number of studies investigated the involvement of NF-κB in sepsis-induced liver injury (40,41). Feng et al (46) demonstrated that the degradation of NF-κB inhibitor α (IκB-α) and the accumulation of NF-κB in the nucleus increased in septic mice, and roflumilast alleviated liver injury by inhibiting the expression of NF-κB and degradation of IκB-α. Those results suggested that NF-κB is closely associated with liver injury in septic mice and liver injury was ameliorated by inhibiting the expression of NF-κB.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-inflammatory mechanisms of roflumilast can be contributed to its PDE4 inhibiting activity; leading to an increase in cAMP concentration and signaling within the epithelial airway and inflammatory cells. The action which in turn will enable roflumilast to suppress the expression of pro-inflammatory cytokines as IL-6 and TNF-α (Feng et al, 2017). Moreover, another study of cigarette smoke-induced pulmonary inflammation in guinea pigs showed that roflumilast could effectively reduce the numbers of neutrophils, lymphocytes and eosinophils in bronchoalveolar lavage fluid (Fitzgerald et al, 2006).…”
Section: Roflumilast and Lung Inflammationmentioning
confidence: 99%
“…Among the released cytokines, IL-6 will play a vital role in the progression of numerous inflammatory reactions as well as endothelial dysfunction and platelets activation (Funakoshi et al, 1999;Liu et al, 2020c). Therefore, cleaving cathepsin G by NEP with reducing associated Ang II formation may be a logical commentary for the suppressed IL-6 expression detected following roflumilast treatment (Feng et al, 2017).…”
Section: Roflumilastmentioning
confidence: 99%